Persistence, Privilege, and Parenting : The Comparative Study of Intergenerational Mobility - Erikson, Robert, 1938-; Jäntti, Markus, 1966-; Smeeding, Timothy M. (Book collections on Project MUSE., 2011)
Americans like to believe that theirs is the land of opportunity, but the hard facts are that children born into poor families in the United States tend to stay poor and children born into wealthy families generally stay rich. Other countries have shown more success at lessening the effects of inequality on mobility possibly by making public investments in education, health, and family well-being that offset the private advantages of the wealth. What can the United States learn from these other countries about how to provide children form disadvantaged backgrounds an equal chance in life? Making comparisons across ten countries, Persistence, Privilege, and Parenting brings together a team of eminent international scholars to examine why advantage and disadvantage persist across generations. The book sheds light on how the social and economic mobility of children differs within and across counties and the impact private family resources, public policies, and social institutions may have on mobility. In what ways do parents pass advantage or disadvantage on to their children? Persistence, Privilege, and Parenting is an expansive exploration of the relationship between parental socioeconomic status and background and the outcomes of their grown children. The authors also address the impact of education and parental financial assistance on mobility. Contributors Miles Corak, Lori Curtus, and Shelley Phipps look at how family economic background influences the outcomes of adult children in the United States and Canada. They find that, despite many cultural similarities between the two countries, Canada has three times the rate of intergenerational mobility as the United States possibly because Canada makes more public investments in its labor market, health care, and family programs. Jo Blanden and her colleagues explore a number of factors affecting how advantages is transmitted between parents and children in the United States and the United Kingdom, including education, occupation, marriage, and health. They find that despite the two nations having similar rates of intergenerational mobility adn social inequality, lack of educational opportunity plays a greater role in limiting U.S. mobility, while the U.K.'s deeply rooted social class structure makes it difficult for the disadvantaged to transcend their circumstances. Hande Waldfogel and Elizabeth Washbrook examine cognitive and behavioral school readiness across income groups and find that pres-school age children in both the UNited States and Britain show substantial income-related gaps in school readiness driven in part by poorly developed parenting skills among overburdened, low-income families. The authors suggest that the most programs int he United States, raising pre-school staff qualifications in Britain, and parenting programs in both countries.